Rock Deformation Estimated by Groundwater-Level Monitoring: A Case Study at the Xianshuihe Fault, China - Yuqing Zhao; You-Kuan Zhang; Xiuyu Liang; Zheming Shi; Yonglin Yang; Feifei Li (Geofluids)
Rock deformations induced by active faults is an important topic in earthquake studies. Such deformations are usually measured with crossfault measurements (CFM), which are time-consuming and labor-intensive. In this study, rock deformations induced by the famous Xianshuihe fault in Xialatuo of China were estimated by groundwater-level monitoring (GLM) and CFM for the period of January 1, 2016 to December 31, 2018. The pattern of the variations in areal strain estimated with GLM matches that from CFM well. The estimated strain by the GLM and CFM both changed from positive to negative with time, indicating that the fault plane switched from tensile to compressive. This indicates that the rate of rock deformation had slowed down during this period, which is consistent with the long-term creep rates obtained by CFM at the site, implying that the fault may have gradually entered the next relock state. The estimated strain changes using the GLM method lag slightly behind those of CFM, which is probably due to the diffusive effects of pore pressure propagation that is caused by the rock deformation under the crustal stress. This study demonstrates that GLM is a more convenient and efficient addition to traditional geophysical techniques and raises the possibility for the characterization of continuous rock deformations. The method may be used to obtain the changing regional strain field with a network of monitoring wells.